The efficiency of the digitalized accounting and payroll services of ReCom Consulting Ltd. - Uz Zaman, Md. Ahsan (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.